2008
DOI: 10.4000/rei.3917
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration economies, spatial dependence and local industry growth

Abstract: The main objective of this paper is to analyse the determinants of employment growth at the local industry level. We estimate an empirical model in order to assess the role of different types of agglomeration economies to local growth controlling also for the presence of spatial dependence. The empirical analysis is applied to the case of Italy and refers to 784 Local Labour Systems and 34 industries (21 manufacturing and 13 services) over the period 1991-2001. Econometric results show that local growth is mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
6
18
0
11
Order By: Relevance
“…These spatial externalities are reflected by the influence of the level of activity of neighbouring regions. This reinforces the evidence found for European regions by Paci and Usai (), Dauth () and Caragliu et al (). Thus, greater diversification and higher employment in neighbouring regions positively affect local growth, suggesting the action of spread effects.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These spatial externalities are reflected by the influence of the level of activity of neighbouring regions. This reinforces the evidence found for European regions by Paci and Usai (), Dauth () and Caragliu et al (). Thus, greater diversification and higher employment in neighbouring regions positively affect local growth, suggesting the action of spread effects.…”
Section: Resultssupporting
confidence: 92%
“…Thus, there is evidence that Brazilian regions are gaining benefits from agglomeration, that is, a higher number of workers in a region. This result is similar to those found by Paci and Usai () and Mameli et al (), for the Italian economy, but different from Combes (), who found that density is negatively associated to employment growth in France.…”
Section: Resultssupporting
confidence: 91%
“…Starting from the original contributions by Glaeser et al (1992) and Henderson et al (1995) for the United States, the literature has investigated the determinants of employment growth, as a proxy for local economic performance, at both the city and the sectoral level. This approach has been applied to various countries and several indicators of local characteristics and factors endowments have been considered in the empirical studies (see among many others, Combes (2000) for French labour systems; Paci and Usai (2008) for the Italian local labour systems).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focus on one of these matters, disregarding the interdependence between them. For example, some scholars focus on detecting the presence of spatial dependence while assuming a linear functional form for the data generating process (Rey and Gallo 2009;Paci and Usai 2008), others only try to assess the existence of nonlinear effects (Ertur and Gallo 2009), some others only control for spatial heterogeneity in a panel framework (Henderson 1997). However, nonlinearities, spatial dependence and spatial heterogeneity are not orthogonal issues and disregarding one of them may generate some biases.…”
Section: Introductionmentioning
confidence: 99%